2022
DOI: 10.3390/microorganisms10102082
|View full text |Cite
|
Sign up to set email alerts
|

Translocation and Dissemination of Gut Bacteria after Severe Traumatic Brain Injury

Abstract: Enterobacteriaceae are often found in the lungs of patients with severe Traumatic Brain Injury (sTBI). However, it is unknown whether these bacteria come from the gut microbiota. To investigate this hypothesis, the mice model of sTBI was used in this study. After sTBI, Chao1 and Simpson index peaking at 7 d in the lungs (p < 0.05). The relative abundance of Acinetobacter in the lungs increased to 16.26% at 7 d after sTBI. The chao1 index of gut microbiota increased after sTBI and peaked at 7 d (p < 0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…This study employed SourceTracker to analyze the microbial composition of PM 2.5 . As a classic microbial traceability tool based on Bayesian algorithm, it has been widely used in medical and health care, soil environment and other fields [ 17 , 18 ]. Here, bacteria and fungi from PM 2.5 samples were considered as “sinks” for traceability, while bacteria and fungi from feed and fecal samples were considered as ‘sources’.…”
Section: Methodsmentioning
confidence: 99%
“…This study employed SourceTracker to analyze the microbial composition of PM 2.5 . As a classic microbial traceability tool based on Bayesian algorithm, it has been widely used in medical and health care, soil environment and other fields [ 17 , 18 ]. Here, bacteria and fungi from PM 2.5 samples were considered as “sinks” for traceability, while bacteria and fungi from feed and fecal samples were considered as ‘sources’.…”
Section: Methodsmentioning
confidence: 99%
“…40 These changes in quantity and/or composition of lung microbiota during disease, also called dysbiosis, can lead to lung inflammation and progression of both acute and chronic pulmonary diseases. 17,20,43,50 Moreover, in disease states the lung microbiome can be seeded by sources other than the oral cavity: with stressors such as sepsis, 51 stroke, 52,53 traumatic brain injury, 54 and critical illness, 55 gut microbes can translocate to the lungs (►Fig. 2), where they are often associated with worse patient outcomes.…”
Section: The Lung Microbiomementioning
confidence: 99%
“…Clinical study has demonstrated that Enterobacteriaceae predominantly constitute the bacterial population responsible for lung infections in patients with brain injuries ( Yang et al., 2023 ). Furthermore, TBI often coexists with intestinal barrier dysfunction and dysbiosis, thereby creating opportunities for the translocation of gut bacteria ( Yang et al., 2022 ). Therefore, the gut microbiota plays a crucial role in the progression of pulmonary inflammation and infection after TBI.…”
Section: Introductionmentioning
confidence: 99%
“…The primary source of lysozyme within the small intestine is derived from Paneth cells, which serve a critical function in maintaining intestinal microbiota homeostasis ( Cray et al., 2021 ). The expression of lysozyme in Paneth cells was found to be reduced after sTBI, leading to an increased bacterial translocation to the lung ( Yang et al., 2022 ). Furthermore, a correlation was observed between the decreased levels of lysozyme and gut bacterial translocation ( Yang et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation